2019
DOI: 10.3390/w11102075
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study of Soluble Reactive Phosphorus Concentration in Fall Creek and Comparison to Northeastern Tributaries of Cayuga Lake, NY: Implications for Watershed Monitoring and Management

Abstract: This study focuses on soluble reactive phosphorus (SRP), a key driver of eutrophication worldwide and a potential contributor to the emerging global environmental problem of harmful algal blooms (HABs). Two studies of tributary SRP concentrations were undertaken in sub-watersheds of Cayuga Lake, NY, the subject of a total maximum daily load (TMDL) development process, due to phosphorus impairment of its southern shelf. The long-term study compared SRP concentration in Fall Creek in the 1970s with that in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has already served as an important baseline, and will continue to do so in the future. Combined with additional data collected after 1995 it has demonstrated the stability of the Fall Creek watershed over long periods of time and under changing conditions, with implications for expected response to management decisions in the broader region (O'Leary et al, 2019). The motivation for the first work on this data set, where particular analytes were selected in collaboration with limnologists studying lake responses to tributary inputs in the early 1970s, is still relevant today as new concerns about the proliferation of harmful algal blooms drive additional watershed studies with the goal of developing predictive models and effective mitigation strategies.…”
Section: Importance Of the Fall Creek Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already served as an important baseline, and will continue to do so in the future. Combined with additional data collected after 1995 it has demonstrated the stability of the Fall Creek watershed over long periods of time and under changing conditions, with implications for expected response to management decisions in the broader region (O'Leary et al, 2019). The motivation for the first work on this data set, where particular analytes were selected in collaboration with limnologists studying lake responses to tributary inputs in the early 1970s, is still relevant today as new concerns about the proliferation of harmful algal blooms drive additional watershed studies with the goal of developing predictive models and effective mitigation strategies.…”
Section: Importance Of the Fall Creek Workmentioning
confidence: 99%
“…Schaffner and Oglesby (1978) examined P loading to lakes and used Fall Creek data to argue that the best calculations of loading reflect forms of P with the most biological significance. Bouldin et al (1975) hypothesized on the relative bioavailability of different forms of P. Their hypothesis was later supported by Prestigiacomo et al (2016) who demonstrated that biologically available P in the region is a composite of completely bioavailable soluble reactive P, mostly bioavailable soluble unreactive P, and less bioavailable particulate P. Haith et al (2012) used work derived from the data set to develop and test a model of phosphorus loading in the Cayuga Lake watershed. The data set was augmented with the results of additional sampling in the 2000's, which led to the finding of no significant change in flow rate‐adjusted soluble reactive P concentration in Fall Creek over many decades. As a result, inter‐annual variation in soluble reactive P loading to Cayuga Lake was determined to be primarily a function of variation in discharge (O'Leary et al, 2019). Seasonal variation in nitrate export was documented by Johnson et al (1976b), and the Fall Creek data also contributed to a comprehensive study of long‐term nitrate dynamics by M. S. Johnson et al (2007).…”
Section: Importance Of the Fall Creek Workmentioning
confidence: 99%